2012
DOI: 10.1159/000335129
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pulmonary Nodules in Ectopic Adrenocorticotropic Hormone Syndrome: Cause or Result?

Abstract: Objective: To report a case of invasive pulmonary aspergillosis mimicking lung cancer with lung to lung metastases in ectopic adrenocorticotropic hormone syndrome (EAS). Clinical Presentation and Intervention: A 60-year-old man suffering from hypokalemic alkalosis, hypertension and limbs paralysis was referred to our hospital. EAS caused by malignancy of lung was highly suspected due to multiple pulmonary nodules presenting on chest film and positron emission tomography (PET) images. Video-assisted thoracic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was reported that the tumors could not be found with a CT scan or an MRI in about 20-50% of the EAS cases (2). The outcomes after lung surgery for suspected tumors were sometimes unsatisfactory, because in these cases the resected nodules were not the ectopic ACTH secreting tumors, but were the results of opportunistic infections, such as invasive pulmonary aspergillosis or bacillosis due to hypercortisolism (5,6). In our cases, four patients could not recover after lobectomy or excision of the mediastinal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the tumors could not be found with a CT scan or an MRI in about 20-50% of the EAS cases (2). The outcomes after lung surgery for suspected tumors were sometimes unsatisfactory, because in these cases the resected nodules were not the ectopic ACTH secreting tumors, but were the results of opportunistic infections, such as invasive pulmonary aspergillosis or bacillosis due to hypercortisolism (5,6). In our cases, four patients could not recover after lobectomy or excision of the mediastinal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeterminate lesions are still one of the most challenging problems in current clinical practice. In such cases, computerized tomography (CT) serves as the standard of reference and its use is recommended for the evaluation of these nodules in the current guidelines [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Although magnetic resonance imaging (MRI) is not used as a first choice in the evaluation of indeterminate nodules, the advantages of using dynamic MRI for tumor catheterization have been demonstrated in several studies [ 9 , 10 ], and due to technical improvements MRI has gained importance for tumor detection and interpretation [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, PJP was mainly described in patients with extreme UFC elevations (> 20 × ULN), it could also manifest with less severe hypercortisolemia (125). Cortisol lowering treatment typically triggers PJP development within a few days (134,135,136), though infection may occur before treatment in severe CS (137,138). For comparison, in patients on GC treatment, median time to immune reconstitution after end of GC therapy is 8 days for fungal and 21-42 days for viral infection (139).…”
Section: Infection Risk Factorsmentioning
confidence: 99%